A brief discussion on the role of calcitonin gene-related peptide in the efficacy of rehabilitation medicine - Zhencheng, Guan; Aiguo, Xue (Frontiers in Rehabilitation Sciences, 2025)
Calcitonin gene-related peptide (CGRP) is an active peptide composed of 37 amino acids that functions through specific receptors. It is widely distributed in small-diameter dorsal root ganglion neurons, trigeminal ganglion neurons, and nerve fibers innervating the spinal cord and brainstem dorsal horn. CGRP regulates various physiological functions, including vasodilation, inflammation modulation, and cardiac protection, and plays a key role in pain transmission. Pain is a global health challenge closely associated with the activity of neuropeptides such as CGRP. Although progress has been made in the application of CGRP in treating various diseases, research in the field of rehabilitation remains in its early stages. This article summarizes the roles of CGRP in peripheral nerve injury, central injury, cardiovascular rehabilitation, and pain rehabilitation. In terms of treatment, common physical therapies such as laser therapy and shock wave therapy have been shown to influence CGRP expression levels. However, the specific effects of these physical interventions on CGRP require more systematic future research and analysis to achieve more efficient and personalized rehabilitation strategies.